Metabolic Syndrome Increases Risk of Barrett Esophagus in the Absence of Gastroesophageal Reflux: An Analysis of SEER-Medicare Data. Issue 4 (April 2015) - Drahos, Jennifer; Ricker, Winnie; Parsons, Ruth; Pfeiffer, Ruth M.; Warren, Joan L.; Cook, Michael B.
Abstract : Goals: To evaluate the association between metabolic syndrome (MetS) and risk of Barrett esophagus (BE) using the Surveillance, Epidemiology, and End Results (SEER)-Medicare linked database compared with 2 control groups—Medicare population controls and endoscopy controls. Background: BE principally arises as an adaptation to the proinflammatory state induced by gastroesophageal reflux disease (GERD). The relationship between obesity and BE is presumed to be mediated by GERD. However, evidence suggests central adiposity also increases risk of BE independent of GERD. Central adiposity is one risk factor defining MetS, which confers a systemic proinflammatory state—a potential GERD-independent mechanism by which obesity could increase the risk of BE. Study: MetS was defined as diagnosis of at least 3 of the following conditions: obesity, elevated triglycerides, high blood pressure, and elevated fasting glucose. Multivariable logistic regression was used to estimate adjusted odds ratios and 95% confidence intervals. Results: In 2198 incident BE cases, prior MetS was significantly associated with BE (odds ratio, 1.20; 95% confidence interval: 1.07, 1.36) compared with population controls. However, GERD status modified the association; among those without prior GERD, MetS increased risk of BE by 34%; however, no association was observed among those with a prior GERD diagnosis ( P -value for effect modification <0.001). MetS was not associated with risk of BE compared with endoscopy controls. Conclusions: MetS increased the risk of BE compared with population controls, an association driven by and confined to the non-GERD stratum. MetS may mediate an association between central adiposity and BE for those without GERD. Abstract : Supplemental Digital Content is available in the text.